PROSES PENGAWASAN OLEH KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI (KPPBC) TIPE MADYA PABEAN B TERHADAP PENYELUNDUPAN BAWANG DI KOTA DUMAI TAHUN 2015-2019 - Santri Juniarti; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Directorate General of Customs (DJBC) is a gate for export and import activity. As the entry and exit gates of commodities, it made Customs Agency known as Trade Facilitator. Import activities are very close with smuggling. Smuggling cause the state has material and non-material losses. The smuggling becomes the main concern of Dumai Custom Service and Supervision Office to oversee the commodities that in and out of this country besides their duty, customs service. The purpose of the research is to know the supervision process by Supervisory Custom Service Office (KPPBC) Middle Type Customs B toward onion smuggling in Dumai year 2015 – 2019 and also to know the obstacles in carry out the duty. This is a qualitative research. The techniques have been used in conducted the research is (1) interview and (2) documentation. The conclusion of this research indicates that the supervision duty by Supervisory Custom Service Office (KPPBC) Middle Type Customs B toward illegal onion has not been done maximally because the supervision has not been done effectively, measurement and the standard of supervision still poor, work evaluation at Customs Office is still not maximal, deviation improvement is not working. Factors that obstruct the implementation of Customs Service office Middle Type Customs B is the insufficient number of executive officers, inadequate patrol boats, and the numbers of People port’s as the entry point of illegal onion.Keywords: standard, working evaluation, deviation improvement